The Fund's Income Position for FY 2009-Midyear Review. (Policy Papers; Policy Paper ;, 2008)
This paper reviews the outlook for the Fund's income position for the financial year 2009 taking into account developments through the first half of the year. The FY 2009 income outlook has improved, mainly as a result of new lending activity associated with the turmoil in global financial markets, together, to a lesser extent, with stronger-than-projected returns in the Investment Account (IA) in the first half of the financial year. The updated projections indicate that the net income position would be slightly positive in FY 2009. However, the actual outcome remains subject to considerable uncertainty related to the timing and amounts of disbursements under current arrangements, as well as potential new arrangements and the performance of the IA.